Collaborative Power of Nrf2 and PPARγ Activators against Metabolic and Drug-Induced Oxidative Injury. (27th August 2017) - Lee, Choongho
Abstract : Mammalian cells have evolved a unique strategy to protect themselves against oxidative damage induced by reactive oxygen species (ROS). Especially, two transcription factors, nuclear factor erythroid 2p45-related factor 2 (Nrf2) and peroxisome proliferator-activated receptor γ (PPAR γ ), have been shown to play key roles in establishing this cellular antioxidative defense system. Recently, several researchers reported ameliorating effects of pharmacological activators for these Nrf2 and PPAR γ pathways on the progression of various metabolic disorders and drug-induced organ injuries by oxidative stress. In this review, general features of Nrf2 and PPAR γ pathways in the context of oxidative protection will be summarized first. Then, a number of successful applications of natural and synthetic Nrf2 and PPAR γ activators to the alleviation of pathological and drug-related oxidative damage will be discussed later.